2021
DOI: 10.1186/s13054-021-03616-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid, disease severity and outcomes in COVID-19

Abstract: Background The severity of coronavirus disease 2019 (COVID-19) is highly variable between individuals, ranging from asymptomatic infection to critical disease with acute respiratory distress syndrome requiring mechanical ventilation. Such variability stresses the need for novel biomarkers associated with disease outcome. As SARS-CoV-2 infection causes a kidney proximal tubule dysfunction with urinary loss of uric acid, we hypothesized that low serum levels of uric acid (hypouricemia) may be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 28 publications
4
16
0
4
Order By: Relevance
“…Interestingly, observational studies of serum urate in patients with COVID-19 have demonstrated that the prevalence of hypouricemia increases following hospital admission for COVID-19 due to proximal renal tubule dysfunction. An inverse association between serum urate levels and disease severity has also been observed in these studies [18,19]. Further research in people with gout and COVID-19 infection are needed to understand whether serum urate levels decline during COVID-19 infection and whether this is associated with adverse outcomes.…”
Section: Key Pointssupporting
confidence: 58%
“…Interestingly, observational studies of serum urate in patients with COVID-19 have demonstrated that the prevalence of hypouricemia increases following hospital admission for COVID-19 due to proximal renal tubule dysfunction. An inverse association between serum urate levels and disease severity has also been observed in these studies [18,19]. Further research in people with gout and COVID-19 infection are needed to understand whether serum urate levels decline during COVID-19 infection and whether this is associated with adverse outcomes.…”
Section: Key Pointssupporting
confidence: 58%
“…Therefore, the change in UA can help to judge the turning point of patients' condition. In a retrospective study using two independent cohorts, among patients with COVID-19 requiring hospitalization, low serum levels of uric acid are common and associate with disease severity and with progression to respiratory failure requiring invasive mechanical ventilation 38 . However, a study cohort included 1854 patients showed that the association between admission serum uric acid and composite outcome of COVID-19 patients was U-shaped.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described an association between high serum uric acid levels and COVID-19 severity, particularly mortality or the rate of using invasive mechanical ventilation (IMV) ( Ghazanfari et al, 2021 ;Zheng et al, 2021 ). However, researchers have also reported an association between low serum uric acid levels and COVID-19 severity ( Dufour et al, 2021 ;Werion et al, 2020 ). Some studies have shown a U-shaped association between serum uric acid levels and the risk of death ( Cho et al, 2018 ;Hu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%